Transition from University to the Labour Market: The Impact of Personal Variables in Graduates’ Perceptions of Self-Efficacy - Liliana Paulos (MDPI AG, 2021)
The transition from university to the labour market is a crucial period for graduates. It is typically characterized by a high degree of uncertainty. Self-efficacy may be a determinant in the process, but the research so far has only considered students or graduates shortly after graduation, strongly compromising its conclusions on the findings. This study aims at exploring the variables which explain the different levels of self-efficacy of graduates in transition to the labour market. A total of 694 graduates who completed their degrees at two Portuguese Higher Education Institutions in the last five years were subjected to a questionnaire. Regression and multivariate analyses based on decision trees (Recursive Partitioning for Classification) showed that (1) older graduates have higher self-efficacy in adapting to work; (2) male graduates have higher self-efficacy in emotional regulation when looking for a job; and (3) graduates with higher grades demonstrated more self-efficacy in job-seeking behaviours. The results also revealed that the graduates’ scientific area, the parents’ level of education and undergoing internships during higher education are also related to self-efficacy. Overall, the study contributed to a better understanding of the construction process of self-efficacy beliefs and its importance in the job-seeking process and in the adaptation to work.